(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Tumors of the brain are referred to by their place of origin, the brain. Tumors are masses ofabnormal tissue that develop inside the skull as a result of unchecked cell division. Brain tumors may alsodevelop as a result of metastasis from cancer originating in other parts of the body. In cases when tumorsare located in the posterior fossa of the skull, the largest ones tend to be found in the cerebralhemispheres. The tumor region can be detected by segmentation of brain Magnetic Resonance Image(MRI).MRI pictures need to be segmented so that the questionable areas may be located. From eachsegmented tissue, significant features are identified utilizing optimized utilizing genetic algorithm.In thisarticle, a bio-inspired optimization method is presented for locating potential tumor sites in an MRI scanof the brain. Bat Optimization Algorithm (BOA) make up the bio-inspired optimization tool (BOA). Thethreshold values for an image are now easily determined by this bio-inspired optimization software.Then, the Fuzzy C clustering technique is used in conjunction with this tool to dynamically determine thethreshold value.